Genetic transformation of Streptococcus pneumoniae by DNA cloned into the single-stranded bacteriophage f1. - Barany, F (1983)
A Staphylococcus aureus plasmid derivative, pFB9, coding for erythromycin and chloramphenicol resistance was cloned into the filamentous Escherichia coli phage f1. Recombinant phage-plasmid hybrids, designated plasmids, were isolated from E. coli and purified by transformation into Streptococcus pneumoniae. Single-stranded DNA was prepared from E. coli cells infected with two different plasmids, fBB101 and fBB103. Introduction of fully or partially single-stranded DNA into Streptococcus pneumoniae was studied, using a recipient strain containing an inducible resident plasmid. Such a strain could rescue the donor DNA marker. Under these marker rescue conditions, single-stranded fBB101 DNA gave a 1% transformation frequency, whereas the double-stranded form gave about a 31% frequency. Transformation of single-stranded fBB101 DNA was inhibited by competing double-stranded DNA and vice versa, indicating that single-stranded DNA interacts with the pneumococcus via the same binding site as used by double-stranded DNA. Heteroduplexed DNA containing the marker within a 70- or 800-base single-stranded region showed only slightly greater transforming activity than pure single-stranded DNA. In the absence of marker rescue, both strands of such imperfectly heteroduplexed DNA demonstrated transforming activity. Pure single-stranded DNA demonstrated low but significant transforming activity into a plasmid-free recipient pneumococcus.